2001
DOI: 10.1073/pnas.211234298
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial overlap between monarch larvae and corn pollen

Abstract: To assess the likelihood that monarch larvae will be exposed to Bacillus thuringiensis (Bt) pollen, we studied milkweed and monarch densities in habitats which comprise much of the land available to breeding monarchs, e.g., cornfields, cornfield edges, other agricultural fields, and nonagricultural areas, in four regions of the monarch breeding range. We found that monarchs use milkweed in cornfields throughout their breeding season, and that per plant densities are as high or higher in agricultural habitats a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
167
1
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(174 citation statements)
references
References 16 publications
5
167
1
1
Order By: Relevance
“…In the USA, milkweed (Asclepiadaceae) growing within maize fields has been shown to provide a resource for larvae of the monarch butterfly, Danaus plexippus (Oberhauser et al 2001). In the UK, within-field weeds are considered to be of little benefit to larvae, particularly in comparison with field-margin vegetation (Feber & Smith 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, milkweed (Asclepiadaceae) growing within maize fields has been shown to provide a resource for larvae of the monarch butterfly, Danaus plexippus (Oberhauser et al 2001). In the UK, within-field weeds are considered to be of little benefit to larvae, particularly in comparison with field-margin vegetation (Feber & Smith 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive follow-up studies thus determined where the monarchs occur during their breeding season [65], and what percentage of the population of monarchs is possibly affected be the Bttoxin in areas where Bt-maize is presently grown [66]. The results showed that larval exposure to pollen on a population-wide basis is low, given the proportion of larvae in maize fields during pollen shed, the proportion of Bt-maize fields, and the levels of pollen within and around maize fields [65]. The proportion of monarch butterfly population exposed to Bt-pollen was estimated to be less than 0.8% [66].…”
Section: Effects Of Bt-crops On Butterfliesmentioning
confidence: 99%
“…It was concluded that the risk of exposure is low and that it is unlikely that Bt-maize will affect the sustainability of monarch butterfly populations in North America [66,67]. Furthermore, several authors claimed that effects of Bt-maize should be compared to mortality caused by other factors, which is very high in natural monarch butterfly populations, and averages around 80% over the entire larval development period [65,67]. More important factors that may influence monarch butterfly survival include loss of over-wintering habitats in Mexico, use of insecticides to control lepidopteran pests and accidents such as collision with automobiles [57].…”
Section: Effects Of Bt-crops On Butterfliesmentioning
confidence: 99%
“…This study led to considerable debate over the environmental impact and relevance for the potential risks from Bt maize. Follow-up studies to investigate the impact of widespread plantings Bt-maize on the Monarch butterfly essentially concluded that the impact of Bt-maize pollen from current commercial hybrids on Monarch butterfly populations is negligible Oberhauser et al, 2001;Pleasants et al, 2001;Sears et al, 2001;Stanley-Horn et al, 2001;Zangerl et al, 2001). This is based on the low expression of Bt toxin genes in pollen for most maize hybrids, lack of acute toxicity at expected field rates, limited overlap of pollen shed and larval activity, and the limited overlap in distribution of Bt-maize and milkweed.…”
Section: Will Gm Crops Have Secondary Ecological Impacts?mentioning
confidence: 99%